The behavior of larval zebrafish reveals stressor-mediated anorexia during early vertebrate development - De Marco, Rodrigo J.; Groneberg, Antonia H.; Yeh, Chen-Min; Treviño, Mario; Ryu, Soojin (Frontiers in Behavioral Neuroscience, 2014)
The relationship between stress and food consumption has been well documented in adults but less so in developing vertebrates. Here we demonstrate that an encounter with a stressor can suppress food consumption in larval zebrafish. Furthermore, we provide indication that food intake suppression cannot be accounted for by changes in locomotion, oxygen consumption and visual responses, as they remain unaffected after exposure to a potent stressor. We also show that feeding reoccurs when basal levels of cortisol (stress hormone in humans and teleosts) are re-established. The results present evidence that the onset of stress can switch off the drive for feeding very early in vertebrate development, and add a novel endpoint for analyses of metabolic and behavioral disorders in an organism suitable for high-throughput genetics and non-invasive brain imaging.